Relative engagement with sources of climate misinformation is growing across social media platforms - Storani, Saverio; Falkenberg, Max; Quattrociocchi, Walter; Cinelli, Matteo (Scientific reports, 2025)
We explore the discourse on climate change across multiple social media platforms, examining the evolution of user engagement with climate-related content and whether this content links to reliable or unreliable news media sources. Through a detailed examination of over 20 million posts on Facebook, Instagram, Twitter, and YouTube over five years (2018–2022), we identify trends in engagement, distinguishing between unreliable and reliable content to assess the impact of misinformation. Further, we investigate the relationships among various discussion topics and their association with information quality, employing a network-based method to quantify the semantic distances between these categories. Our findings reveal diverse trends in engagement that align with global events, suggesting that social media discussions promptly reflect the resonance of real life events concerning climate change such as COP26, the Climate Action Week and climate strikes associated with the Fridays for Future movement. Notably, despite the lower volume of content linking to unreliable sources, we observe significantly greater relative engagement with these sources compared to content from reliable sources on all platforms except Twitter. This highlights a persistent challenge in the online discourse surrounding climate misinformation.